Comparative Study of Management Information Systems in Cement Companies in Southeast Nigeria, South Sulawesi, Kenya - Ayunda, Ajenk; Hakim, Nur; Supratikta, Hadi (Journal of Investment Development, Economics and Accounting, 2024)
This study explores the impact of Management Information Systems (MIS) and technological innovations on the performance of cement manufacturing firms in Southeast Nigeria, South Sulawesi, and Kenya. This study examines the use of management information systems in the cement industries of Southeast Nigeria, South Sulawesi, and Kenya using a literature review methodology. Through a comprehensive literature review of three key journals, the findings reveal a significant positive correlation between the use of decision support systems, transaction processing systems, and executive support systems, and the enhancement of corporate performance. In Southeast Nigeria, these systems increased firm performance by 0.321, 0.496, and 0.501 respectively. Impact of information technology on agency capacity in the cement industry in South Sulawesi. The effect of information technology on body skills is 0.267 and p-value 0.025, it has a significant effect on the statement, which proves that information technology has a direct effect on the body. They have the ability to support movement. In Kenya, the adoption of strategic and technological innovations notably improved sales volumes, operational efficiency, and cost reduction, with a mean aggregate score of 4.12 from surveyed department heads. The findings underscore the importance of strategic innovations tailored to specific industry needs and the necessity of training programs to equip employees with essential technical skills. This research provides actionable insights for cement firms aiming to enhance their competitive edge and achieve sustainable growth in a dynamic global market.